Benzoic Acid and Sorbic Acid in Noodles in Nakhon Ratchasima Municipality - Inchai, Sirintip; Sitthiopagul, Somchai (Journal of Health Science of Thailand, 2017)
Benzoic acid and sorbic acid are the common preservatives using in many kinds of food. The levels of benzoic acid and sorbic acid in noodles in Nakhon Ratchasima municipality during October 2005 to September 2006 were studied. In all, 300 samples were analysed and the result showed that benzoic acid was found in 283 samples (94.3%), ranging of from 0.0 to 5,117.1 mg/kg or 1,201.0 mg/kg on the average. The average levels of benzoic acid found in big - stripped noodles, small - stripped noodles, egg noodle, noodle soup and plain soup were 2,180.1, 1,958.4, 279.2, 1,241.0 and 146.6 mg/kg respectively. The average level of sorbic acid found in noodle soup was 4.1 mg/kg. Sorbic acid was not found in noodle strips and plain soup. Of all the samples, more than 1,000 mg/kg of benzoic acid were found in 125 samples (41.7%).